2010
DOI: 10.1039/c0cc01008a
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature spin crossover and Langmuir–Blodgett film formation of an iron(ii) triazole complex featuring a long alkyl chain substituent: the tail that wags the dog

Abstract: Publication informationChemical Communications, 46 (35)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 22 publications
2
48
0
3
Order By: Relevance
“…This can be archived by covalently attaching appropriate ligands and complexes to nano-particles or flat surfaces; through the formation of polymers or by forming thin films using Langmuir-Blodgett (LB) techniques. 17 Herein we describe out efforts in bridging these two areas of research by employing lanthanide directed synthesis (using ligands 1 and 2) in the formation of chiral luminescent lanthanide amphiphilic complexes, and their use in the formation of LB films, the properties of which can be probed by using circular polarized luminescence (CPL). The ligands were designed to include a terdentate coordination pocket with a closely associated sensitizing antenna (i.e.…”
mentioning
confidence: 99%
“…This can be archived by covalently attaching appropriate ligands and complexes to nano-particles or flat surfaces; through the formation of polymers or by forming thin films using Langmuir-Blodgett (LB) techniques. 17 Herein we describe out efforts in bridging these two areas of research by employing lanthanide directed synthesis (using ligands 1 and 2) in the formation of chiral luminescent lanthanide amphiphilic complexes, and their use in the formation of LB films, the properties of which can be probed by using circular polarized luminescence (CPL). The ligands were designed to include a terdentate coordination pocket with a closely associated sensitizing antenna (i.e.…”
mentioning
confidence: 99%
“…Unfortunately, a pure sample of the complex of pgdpt , [Fe II ( pgdpt ) 2 (NCBH 3 ) 2 ], proved elusive because instead it formed mixtures of the desired complex and starting material [Fe(pyridine) 4 (NCBH 3 ) 2 ]. Hence, although we have previously shown that Rdpt ‐type ligands suitably functionalised with long‐alkyl chain tails are capable of forming stable Langmuir films, and it is known from other studies that PEG tails can also confer film‐forming properties, such studies have not been performed on the pgdpt system.…”
Section: Resultsmentioning
confidence: 99%
“…In this proof of principle study, we go on to demonstrate the versatility of apdpt as a reactive precursor, by easily appending three quite different types of functional groups, which is the first step for future studies that will aim for spin‐state‐dependent emission, covalent binding of SCO‐active complexes to gold surfaces, or the formation of SCO‐active films through Langmuir–Blodgett techniques . The synthesis, characterisation and magnetic properties of the resulting complexes is also presented herein, along with the successful formation of Rdpt ‐coated gold nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore the potential of the Ln complexes for photonic applications it is advantageous to incorporate them in an inert host matrix due to dissolution or dispersion of discrete lanthanide complexes in a polymer matrix or attachment of the lanthanide complexes to the polymer matrix through covalent bonds [7]. Recent attempts have been reported to find a route by forming thin films using Langmuir-Blodgett (LB) techniques [8,9]. Here, we present the syntheses, characterization and luminescent properties of Langmuir-Blodgett (LB) films based on homoand heteroleptic terbium(III) complexes with 1-phenyl-3-methyl-4-stearoylpyrazolone-5 (HL) and 1-phenyl-3-methyl-4-formylpyrazolone-5 (HL 0 ).…”
Section: Introductionmentioning
confidence: 99%